Impact of BMI on Ability to Successfully Create an IPAA. Issue 11 (November 2016) - Khasawneh, Mohammad A.; McKenna, Nicholas P.; Abdelsattar, Zaid M.; Johnson, Angela; Dozois, Eric J.; Pemberton, John H.; Mathis, Kellie L.
Abstract : BACKGROUND: IPAA is the surgical treatment of choice for patients with ulcerative colitis. Limited data exist on how obesity impacts the ability of the surgeon to successfully create an IPAA. OBJECTIVE: We aimed to determine how BMI affects the ability to successfully complete the operation. DESIGN: This was a retrospective cohort study. SETTINGS: The study was conducted at a single tertiary care center. PATIENTS: We included all of the patients undergoing an IPAA for ulcerative colitis between January 2002 and August 2013 at our institution. A total of 1175 patients underwent proctocolectomy for ulcerative colitis during the study period; 129 were not offered IPAA (reasons included patient preference (n = 53), advanced age/comorbidity (n = 28), obesity (n = 23), incontinence (n = 8), suspicion of Crohn's disease (n = 8), rectal cancer (n = 3), and other (n = 6)). Twenty-six patients had a concurrent cancer diagnosis, and 5 had a polyposis syndrome. MAIN OUTCOME MEASURES: We used logistic regression modeling to estimate the association between BMI and unsuccessful pouch attempts. RESULTS: Of the 1046 patients offered IPAA, 19 (1.82%) could not be technically completed at the time of surgery. Increasing BMI was associated with a higher risk of not being able to technically perform IPAA (OR = 1.26 (95% CI, 1.17–1.34)). The chance of an unsuccessful pouch rose from 2.0% at a BMI of 30 to 5.7% at a BMI of 35 and 15.0% at a BMI of 40 ( p < 0.01). The area under the receiver operator characteristics curve was 0.82. BMI explained 21% of the variation in pouch success rate. LIMITATIONS: This study is limited in its generalizability. Also, the verbosity within the operative dictations varied among surgeons, making it impossible to be certain which maneuvers were performed to gain length in each patient. In addition, we were limited to BMI as a surrogate for visceral obesity, and we did not include medical therapy at the time of IPAA attempt. CONCLUSIONS: There is a strong association between increasing BMI and the ability to technically perform IPAA. Obese patients should be counseled to lose weight preoperatively to increase the probability of successful IPAA construction at the time of operation.